Propuesta de pliego tarifario para el cobro del servicio de agua potable a partir del estudio técnico realizado por la EMMAP-EP - Delgado Sacón, Andrea Michelle (2021)
The objective of this research was to design a proposal for a tariff schedule for the collection of the drinking water service based on the technical study carried out by the Public Joint Venture of Potable Water of the Bolívar, Junín, San Vicente, Sucre and Tosagua cantons that allows the sustainability of the company. The methodology used was the theoretical and analytical one with which the proposal could be made, methods such as deductive, inductive and analytical were used, these allowed to obtain the necessary information to meet the objectives set, also an interview with the person in charge was used as a tool of the technical study carried out in the institution, through this it was possible to know the current situation of the entity, the problems they have with their current rates and if the institution complies with the standards established in the regulation DIR-ARCA-RG-006- 2016, and the creation of it. Later very important tools were applied such as; consumer category, consumption blocks, and fixed - variable charges, which are key elements that allowed determining the tariff schedule in said company. It is very important to design new rates for the collection of the service offered, which must be governed by the Water Regulation and Control Agency so that the processes are carried out as established by law. Finally, the new proposal was presented to the directors of the institution for their respective consideration.